A qualitative fallacy: Life trapped in interpretations and stories. (June 2023) - Bøe, Tore Dag; Bertelsen, Bård; Larsen, Inger Beate; Topor, Alain
This paper points out some problematic aspects of qualitative research based on interviews and uses examples from mental health. The narrative approach is explored while inquiring if the reality of life here is forced into the formula of a chronological story. The hermeneutic approach, in general, is also examined, and we ask if the reality of life in this scenario becomes caught up in a web of interpretations. Inspired by ideas from Bakhtin and phenomenology, we argue for interview-based research that stays with unresolvedness and constantly question the web of interpretations and narratives that determine our experiences. This also chimes with certain dialogical practices in mental health in which tolerance of uncertainty is the guiding principle. Concludingly, we suggest that interview-based research could be a practice of 'un-resolving' in which researchers, together with the participants, look for cracks, contradictions, and complexities to prevent the qualitative fallacies of well-organized meanings and well-composed stories.